PENGARUH SERVICE EXCELLENCE, CUSTOMER EXPERIENCE DAN BRAND TRUST TERHADAP CUSTOMER LOYALTY (Studi Kasus Pengguna Jasa Grab di Kota Bengkulu) - Ratnawili Ratnawili; Marliza Ade Fitri; Eti Arini (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2021)
ABSTRACTThis study aimed to determine the effect of Service Excellence, customers’ experience and Brand Trust toward customers’ loyalty to Grab service users Bengkulu city. This study used a sample of 95 online grab motorcycle taxi consumers in Bengkulu city. The data collection techniques used a questionnaire. The analysis technique of this study used multiple linear regression, coefficient of determination and hypothesis testing. The results of multiple regression research show a positive direction, namely Y = 0.261 + 0.209 X1 + 0.335X2 + 0.261 X3. The determination coefficient test of the adjusted R square is 0.476. This means that X1 (Service Excellence), X2 (customers’ experience) and X3 (Brand Trust) have a contribution to customers’ loyalty (Y) by 47.6% while the remaining 52.4% is influenced by other factors that are not examined in this research. The results of the hypothesis test partially show that Service Excellence has a positive and significant effect toward customers’ loyalty to Grab service users in Bengkulu city. Customers’ experience has a positive and significant impact on customers’loyalty to Grab service users in Bengkulu city. Brand Trust has a positive and significant effect toward customers’ loyalty to Grab service users in Bengkulu city. Simultaneous hypothesis test results show that Service Excellence, customerS’ experience and Brand Trust have a positive and significant effect toward customers’ loyalty to Grab service users in Bengkulu city.Keywords: Satisfaction, Trust, and Purchase Intention